INDICES AND RATING AS INDICATORS OF PERIPHERALITY MEASUREMENT OF UKRAINIAN SOCIO-POLITICAL DEVELOPMENT (2014-2017) - Гулай, В. В.; Дзера, М. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The purpose of the article is to analyze the indexes and rating assessments as indicators of measuring the dominant peripheral model of socio-political development of Ukraine after the Revolution of Dignity victory. The main focus is on discovering the nature of the simulation of social and political change primarily instruments of international human development index, and perceptions of democracy and anti-corruption, demonstrating the obvious lack of quantitative indicators and qualitative irreversibility of the reform policy, declared post-maydan old / new ruling class. According to the authors, the continuation of the Ukrainian further stay in the zone of socio-political turbulence includes a powerful risk potential for the state security, society and individual in political, social, economic and informational dimensions.